Modulation of alternative splicing by expression of small nuclear ribonucleoprotein polypeptide N. (14th October 2014) - Lee, Moon‐Sing; Lin, Yu‐Shan; Deng, Yi‐Fang; Hsu, Wan‐Ting; Shen, Chiung‐Chun; Cheng, Yi‐Hsin; Huang, Yao‐Ting; Li, Chin
<x xml:space="preserve">Abstract</x> Alternative splicing of pre‐mRNA, catalyzed by small nuclear ribonucleoproteins (snRNPs), plays an important role in proteome complexity and the modulation of cellular functions. snRNP polypeptide N (SmN), is tissue‐specifically expressed, where it replaces snRNP polypeptide B (SmB)/B′ in the Sm core assembly of snRNPs. Recent studies have demonstrated that perturbation of snRNPs leads to alternative splicing, but whether SmN modulates functions of the splicing machinery remains unclear. In this study, we found that ectopic expression of SmN increased utilization of the proximal 5′ splice site on an adenovirus early gene 1A reporter. To evaluate the molecular mechanisms underlying SmN‐dependent alternative splicing, we generated a HeLa cell line with an inducible expression system for SmN. Upon SmN induction, SmB/B′ expression decreased dramatically, despite only small changes in the level and splicing pattern of SNRPB mRNA. In addition, SmN was incorporated into the U2 snRNP but not into the U1 snRNP after induction. Sedimentation analysis revealed a decrease in the level of mature U2 snRNP. This result suggests that SmN incorporation into the Sm core may impede processing, decreasing the level of functional U2 snRNP. We also found that the inclusion frequencies of alternatively spliced exons in the bridging integrator 1 and exocyst complex component 7 (EXOC7) genes were modulated by SmN expression. An enhanced GFP–EXOC7 reporter was used to confirm that SmN increases the inclusion frequency of EXOC7 exon 7. Taken together, our findings indicate that SmN expression reduces the level of mature U2 snRNP, leading to alternative splicing.